OsAT1, an anion transporter, negatively regulates grain size and yield in rice. Issue 3 (13th May 2022) - Liu, Kun; Wang, Xin; Liu, Hengchen; Wu, Jiarui; Liang, Feng; Li, Shaobo; Zhang, Jianjun; Peng, Xinxiang
Abstract: Improving the grain yield of rice is a central goal of basic and applied scientific research. Here, we identified an anion transporter, OsAT1, localized in the endoplasmic reticulum and Golgi. OsAT1 is highly expressed in flag, stem, and sheath as monitored using qRT‐PCR and p OsAT1 ::GUS. Thousand‐grain weight, grain weight per plant, and content of starch were significantly increased in OsAT1 knock‐down mutants ( OsAT1 ‐Ri) but significantly decreased in OsAT1 overexpressed lines ( OsAT1 ‐OE). In addition, the grain weight per plant increased by 6.17% to 6.78% in OsAT1 ‐RNAi lines, whereas it decreased by 45.93% to 46.76% in OsAT1 ‐OE lines, compared to wild‐type. Moreover, the copper content was noticeably reduced in flag leaf of OsAT1 ‐Ri lines and increased in OsAT1 ‐OE lines. RNA‐sequencing analysis of OsAT1‐ OE lines revealed that the genes related to starch biosynthesis and metabolism pathway were enriched in the down‐regulated category. Thus, our results suggest that knock‐down of OsAT1 in rice possibly reduces copper accumulation and improves the accumulation of storage starch, hence, increasing the grain size and weight. OsAT1 may be a useful gene to consider for cereal breeding programs.